Design optimization studies on high torque and high power density hybrid excitation flux switching motor for HEV - Erwan, Sulaiman, Dr.; M. Z., Ahmad; Kosaka, T.; Matsui, N. (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.